THE EFFECT OF THE IMPLEMENTATION OF THE SCHOOL LITERACY MOVEMENT ON INTEREST IN CONTINUING EDUCATION TO HIGHER EDUCATION AT SMA DHARMA BHAKTI PALEMBANG - Sari, Atika Permata; Annur, Saipul; Yuniar, Yuniar (LP2M IAI Al-Khairat Pamekasan, 2025)
This research aims to determine the influence of the implementation of the school literacy movement on interest in continuing education to higher education at SMA Dharma Bhakti Palembang. This research aims to analyze the influence of the implementation of the school literacy movement on students' interest in continuing their education to higher education at SMA Dharma Bhakti Palembang. The research method used is quantitative research, mostly carried out using statistical methods, which are used to collect quantitative data from research studies. The results of this research, the School Literacy Movement has a positive influence on Interest in Continuing Higher Education, are partially accepted. Based on the simple linear regression equation above, it can be concluded that the School Literacy Program variable (X) has an average results in its influence on Interest in Continuing Higher Education (Y2) at SMA Dharma Bhakti Palembang.